1987
DOI: 10.1017/s0950268800066504
|View full text |Cite
|
Sign up to set email alerts
|

A demographic survey of campylobacter, salmonella and shigella infections in England: A Public Health Laboratory Service Survey

Abstract: Five laboratories serving a population of 1.5 million participated in a 2-year survey of campylobacter, salmonella and shigella infections in patients suffering from gastrointestinal symptoms. In total, 33,857 faecal specimens were examined of which 5.5% yielded campylobacters, 3.4% salmonellas and 0.8% shigellas; incidence of infection (per 100,000 population per year) was 58, 38 and 9 respectively. Peak incidences occurred at different ages for each organism: campylobacter, 1-4 years (183); salmonella, less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
54
2
5

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 10 publications
7
54
2
5
Order By: Relevance
“…The high rates of infection in children were expected, but not in young adults; 365 % of all isolates were obtained from adults aged between 20 and 39 years (Table 2). This is similar to the pattern found in Europe and North America [13][14][15]. In most African, Middle Eastern and developing countries transmission is so high that children become immune by the time they are 5 years old, and clinically apparent infection is almost unknown in adults [8,16].…”
Section: Discussionsupporting
confidence: 82%
“…The high rates of infection in children were expected, but not in young adults; 365 % of all isolates were obtained from adults aged between 20 and 39 years (Table 2). This is similar to the pattern found in Europe and North America [13][14][15]. In most African, Middle Eastern and developing countries transmission is so high that children become immune by the time they are 5 years old, and clinically apparent infection is almost unknown in adults [8,16].…”
Section: Discussionsupporting
confidence: 82%
“…Numerous surveillance studies of non-typhoid Salmonella (NTS) infections in developed countries have reported a distinct seasonal variation, with peaks and troughs occurring in the warmer and colder months respectively [1][2][3][4][5][6][7]. Higher incidence in warmer months has been explained by exogenous risk factors, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In humans the bacteria have been associated with gastro-duodenal ulcer (H. pylori), proctocolitis in homosexuals (C. cinaedi and C. fennelliae) [3][4][5][6] but mainly acute enteritis, in which C. jejuni is the most frequently detected biotype alongside C. coli, C. lari, 'C. upsaliensis' and C. hyointestinalis [7][8][9][10][11][12]. The campylobacters responsible for diarrhoea are also called thermophilic, as they grow at 42 'C.…”
Section: Introductionmentioning
confidence: 99%